1980
DOI: 10.1073/pnas.77.4.1877
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for RNA splicing.

Abstract: ABSrRACT The most abundant of the stable small nuclear RNAs of eukaryotic cells, U-1 small nuclear RNA, is exactly complementary to the consensus sequences at RNA splice sites.We propose that this RNA is the recognition component of the nuclear RNA splicing enzyme and forms base pairs with both ends of an intron so as to align them for cutting and splicing.Intramolecular RNA splicing, first discovered for the adenovirus-specific RNA (1-3), occurs in the expression of numerous eukaryotic genes (4). At present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
162
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(165 citation statements)
references
References 43 publications
2
162
0
1
Order By: Relevance
“…These consensus sequences, termed the donor site or 5h splice site [5h (C\A)AGGU(A\-G)AGU 3h] and acceptor site or 3h splice site [5h (U\C)11N-(U\C)AG(G\A) 3h], signal the precise location for excision by the spliceosome and subsequent removal of an intron [24,25]. The two splice sites overlap the intron\exon boundaries.…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%
“…These consensus sequences, termed the donor site or 5h splice site [5h (C\A)AGGU(A\-G)AGU 3h] and acceptor site or 3h splice site [5h (U\C)11N-(U\C)AG(G\A) 3h], signal the precise location for excision by the spliceosome and subsequent removal of an intron [24,25]. The two splice sites overlap the intron\exon boundaries.…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%
“…For example, Ul RNA has been linked to mRNA splicing (Lerner et al, 1980;Rogers and Wall, 1980) while the RNA moiety of RNAase P has been shown to be absolutely required for its activity (Kole et al, 1980). RNA has even been shown to be capable of making and breaking phosphodiester bonds in the complete absence of protein (Kruger et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…For M2 mRNA, the junction is between nucleotides 51 and 740; for mRNA3, the junction is between nucleotides 11 and 740. More complicated consensus sequences involving nucleotides complementary with the U1 small nuclear RNA have been observed (20,21 Al and A2, probable 3' junctions of the intervening sequences, which are the same for M2 mRNA and mRNA3.…”
mentioning
confidence: 99%